Feasibility, acceptability, and appropriability of a national whole-school program for reducing school violence and improving school coexistence - Rojas-Andrade, Rodrigo; Lopez Leiva, Verónica; Varela, Jorge J.; Soto García, Pamela; Álvarez, Juan Pablo; Ramirez, María Teresa (Frontiers in Psychology, 2024)
Introduction The increase in school violence following the COVID-19 pandemic underscores the need for schools to adopt a multilevel whole-school approach. This study examines a national program designed by the Chilean Ministry of Education, in collaboration with universities, as part of the Ministry’s Educational Reactivation Plan, aimed at improving school climate management across Chile. Methods The “Learning to Live Together Program” (LLT) was implemented across all 16 regions of Chile, focusing on establishing school climate networks, providing direct intensive university technical assistance, and enhancing professional development and training. The feasibility, acceptability, and appropriability of the LLT program were assessed through a survey distributed to 1,561 staff members from 783 schools. Participants responded to a comprehensive set of instruments measuring acceptability, appropriability, feasibility, attitudes toward implementation, fidelity, and initial perceived results. Results The results indicate high initial adoption rates and significant improvements in the assessed dimensions. The enhancement of school climate practices and strengthening school collaboration networks were of considerable relevance. Discussion These findings support the efficacy of the multilevel whole-school approach as a viable strategy for Latin American countries, providing critical data for educational and governmental decision-making. Furthermore, this study provides evidence that these outcomes may be applicable to the implementation of similar policies in different contexts and countries.